Antimicrobial Activity of Essential-Oil-Based Nanostructured Lipid Carriers against Campylobacter Spp. Isolated from Chicken Carcasses - Henrique Machado Pires; Luciana Machado Bastos; Elenice Francisco da Silva; Belchiolina Beatriz Fonseca; Simone Sommerfeld; Robson José de Oliveira Junior; Lígia Nunes de Morais Ribeiro (MDPI AG, 2024)
Campylobacter is a virulent Gram-negative bacterial genus mainly found in the intestines of poultry. The indiscriminate use of traditional antibiotics has led to drug resistance in these pathogens, necessitating the development of more efficient and less toxic therapies. Despite their complex biologically active structures, the clinical applications of essential oils (EOs) remain limited. Therefore, this study aimed to increase the bioavailability, stability, and biocompatibility and decrease the photodegradation and toxicity of EO using nanotechnology. The diffusion disk test revealed the potent anti-Campylobacter activity of cinnamon, lemongrass, clove, geranium, and oregano EOs (>50 mm). These were subsequently used to prepare nanostructured lipid carriers (NLCs). Formulations containing these EOs inhibited Campylobacter spp. growth at low concentrations (0.2 mg/mL). The particle size, polydispersity index, and zeta potential of these systems were monitored, confirming its physicochemical stability for 210 days at 25 °C. FTIR-ATR and DSC analyses confirmed excellent miscibility among the excipients, and FE-SEM elucidated a spherical shape with well-delimited contours of nanoparticles. The best NLCs were tested regarding nanotoxicity in a chicken embryo model. These results indicate that the NLC-based geranium EO is the most promising and safe system for the control and treatment of multidrug-resistant strains of Campylobacter spp.